EVALUASI DAMPAK RUBBER DEPOSIT DI PERKERASAN RIGID PADA RUNWAY SELATAN 07R/25L DI BANDARA INTERNASIONAL SOEKARNO-HATTA - Bahri, Muhammad; Oemar, Fatmawati; Rachmat, Tri (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2024)
Rubber deposit is a layer of rubber that forms on runway pavement as a result of the friction of aircraft wheels during landing and takeoff. Rubber eroded from aircraft tires will stick to the pavement and over time, can form a thick layer of rubber that can affect runway performance. As a result of the very busy number of flights at Soekarno-Hatta International Airport, this has resulted in a buildup of aircraft tire rubber residue on the runway and has become a problem for flight safety. The aim of this research is to evaluate the impact of rubber deposits on rigid pavement on the 07R/25L South Runway at Soekarno-Hatta International Airport. The aim of this research is to evaluate the impact of rubber deposits on rigid pavement on the 07R/25L South Runway at Soekarno-Hatta International Airport. The data or information used is secondary data obtained from the airfield unit in Angkasapura II Soekarno-Hatta Airport, Tangerang. The data processing method uses quantitative processing to obtain the average thickness of the rubber deposit. The results of this research are to show the height of rubber deposits resulting from aircraft movements on Runway 07L/25R, where the highest values are for Boeing 737- 800 type aircraft and Airbus A320 aircraft. This is influenced by the number of aircraft movements which tend to be dominant compared to other types of aircraft. The solution for cleaning rubber deposits is done using water blasting.